The monks of the West, from St. Benedict to St. Bernard - Montalembert, Charles Forbes (Patrick-Donahoe, 1872)
v. 1. Dedication. Introduction. book I. The Roman Empire after the peace of the church. book II. Monastic precursors in the East. book III. Monastic precursors in the West. 1861.--v. 2. book IV. St. Benedict. book V. St. Gregory the Great. Monastic Italy and Spain in the sixth and seventh centuries. book VI. The monks under the first Merovingians. book VII. St. Columbanus. The Irish in Gaul and the colonies of Luxeuil. 1861.--